TESS first look at evolved compact pulsators : Asteroseismology of the pulsating helium-atmosphere white dwarf TIC 257459955 - Bell, Keaton J. (2019)
Context. Pulsation frequencies reveal the interior structures of white dwarf stars, shedding light on the properties of these compact objects that represent the final evolutionary stage of most stars. Two-minute cadence photometry from the Transiting Exoplanet Survey Satellite (TESS) records pulsation signatures from bright white dwarfs over the entire sky. Aims. As part of a series of first-light papers from TESS Asteroseismic Science Consortium Working Group 8, we aim to demonstrate the sensitivity of TESS data, by measuring pulsations of helium-atmosphere white dwarfs in the DBV instability strip, and what asteroseismic analysis of these measurements can reveal about their stellar structures. We present a case study of the pulsating DBV WD 0158−160 that was observed as TIC 257459955 with the two-minute cadence for 20.3 days in TESS Sector 3. Methods. We measured the frequencies of variability of TIC 257459955 with an iterative periodogram and prewhitening procedure. The measured frequencies were compared to calculations from two sets of white dwarf models to constrain the stellar parameters: the fully evolutionary models from LPCODE and the structural models from WDEC. Results. We detected and measured the frequencies of nine pulsation modes and eleven combination frequencies of WD 0158−160 to ∼0.01 µHz precision. Most, if not all, of the observed pulsations belong to an incomplete sequence of dipole (` = 1) modes with a mean period spacing of 38.1 ± 1.0 s. The global best-fit seismic models from both LPCODE and WDEC have effective temperatures that are &3000 K hotter than archival spectroscopic values of 24 100–25 500 K; however, cooler secondary solutions are found that are consistent with both the spectroscopic effective temperature and distance constraints from Gaia astrometry. Conclusions. Our results demonstrate the value of the TESS data for DBV white dwarf asteroseismology. The extent of the shortcadence photometry enables reliably accurate and extremely precise pulsation frequency measurements. Similar subsets of both the LPCODE and WDEC models show good agreement with these measurements, supporting that the asteroseismic interpretation of DBV observations from TESS is not dominated by the set of models used. However, given the sensitivity of the observed set of pulsation modes to the stellar structure, external constraints from spectroscopy and/or astrometry are needed to identify the best seismic solutions.